Patterns in interpreting the novel compound nouns among L2 learners / Zeenath Begum binti Akbar Khan - Akbar Khan, Zeenath Begum (2014)
This study aims to investigate the pattern of interpretation used by Malay and Indian L2 learners in interpreting novel compound nouns. Next, this study aims to identify the similarities and differences between Malay and Indian L2 learners on the factors affecting their acquisition of L2 and the interpretations of novel compound nouns. Similarly, this study aims to identify the influence of learners’ first language in the interpretation of novel compound nouns. Data were collected from 19 Malay and 15 Indian students whose native languages are Malay and Tamil, respectively. A novel compound noun test and a questionnaire were used for data collection. The findings revealed that property interpretation in dual-process theory (Wisniewski, 1996) was used more than relation interpretation in Carin theory (Gagne and Shoben, 1997) when interpreting novel compound nouns. The findings are in support of the claim made by Wisniewski (1996) in his dual-process theory that property interpretations are also common and frequently used in interpreting novel compound nouns like relation interpretations. The finding of this study also revealed that there are some similarities and differences on the factors that affect the interpretations of novel compound nouns among Malay and Indian L2 learners. Another finding revealed that Tamil language has a higher influence on its users than Malay language in interpreting novel compound nouns.